ВЛИЯНИЕ ПРОЦЕССА ЭКСТРАКЦИИ НА ФИЗИКО- ХИМИЧЕСКИЕ СВОЙСТВА ЭКСТРАКТА ЧАЙНОГО ЛИСТА, ВЫРАЩЕННЫХ В УСЛОВИЯХ ЛЕНКОРАНСКО-АСТАРИНСКОГО РЕГИОНА АЗЕРБАЙДЖАНСКОЙ РЕСПУБЛИКИ (World Science, 2019)
The object of the study has been a fresh leaf of green tea grown in the Lenkoran-Astara zone of the Republic of Azerbaijan, dried green and black tea and liquid and dry extract based on them. In order to study the effect of technological parameters on extractiveness, the following factors have been selected: temperature, extraction time, hydraulic module (ratio of raw material to extractant). The density of the obtained extract has been determined by the pycnometer method, the viscosity by viscometers of various diameters, and the dry matter content by the refractometric method. The results of experimental studies show that the optimum conditions for the transition of the maximum amount of extractive substances to a solvent during the extraction of black and green tea with water are 363.15 K, the extraction time is 180-200 min, and the ratio of raw material to extractant (hydraulic module) is 1:20.